Propensity of green consumption behaviors in representative cities in China. (1st October 2016) - Li, Yan; Lu, Yi; Zhang, Xiyue; Liu, Leping; Wang, Minghan; Jiang, Xiaoqun
Abstract: Green consumption behaviors are based on consumers' attitude. However, there is a gap between them. Improving green consumption attitude will to a large extent affect the acceptance of green consumption. The study interviewed consumers in four representative cities in China through questionnaires, which was to search for a solution that affect consumers' willingness to pay for green products by employing a multivariate logistic regression. Furthermore, an empirical analysis was made to study their green consumption behaviors. It is shown that Chinese consumers have already been aware of green consumption to a certain extent and that green consumption willingness is influenced by age, location, sources of information, and a host of other factors. At present, nearly half of the consumers are willing to pay an extra of no more than 5% for green products, which is lower than the premium price for green products relative to non-green ones. However, the actual premium price of green products in China exceeds this level in general, rendering green products a less advantageous position in markets. Approaches including multiple marketing channels, trade-in services, and green branding can effectively raise consumers' reserve price for green products. Highlights: Green consumption intention and consumers' age have positive correlation. Near a half consumers are willing to pay under 5% for green products. There is a gap between green consumption behavior and intention because of green product prices. Widening marketing channels could be helpful for improving WTP.